(untitled) (Homoeopathy for All, 2021)
Urinary tract infection (UTI) is one of the most common pediatric infections. It distresses the child, concerns the parents, and may cause permanent kidney damage. The condition can occur occasionally or recur frequently. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.